2007
DOI: 10.4161/cbt.6.5.3975
|View full text |Cite
|
Sign up to set email alerts
|

Calcium/calmodulin-dependent kinase II plays an important role in prostate cancer cell survival

Abstract: It has recently been shown that the androgen receptor (AR) is the main factor that required for prostate cancer cells survival. We show that knocking down AR expression by siRNA induces PI3K-independent activation of Akt, which was mediated by calcium/calmodulin-dependent kinase II (CaMKII). We further show, for the first time, that prostate cancer cells express beta,gamma and delta CaMKII genes, and the expression of these genes is under the control of AR activity: active AR in the presence of androgens inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 54 publications
(75 reference statements)
5
75
0
Order By: Relevance
“…As can be seen from Figure 3D, only KN-93 showed a dose-dependent inhibition of p53-Ser15 phosphorylation; there is some inhibition with STO-609, but only at high concetration (50 μM). We subsequently treated LNCaP-mock and LNCaP-CaMKII-β transfectant cells 17 with DOX in the presence of si-AR and found that CaMKII-β overexpression protected p53-Ser15 expression (Fig. 3E).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…As can be seen from Figure 3D, only KN-93 showed a dose-dependent inhibition of p53-Ser15 phosphorylation; there is some inhibition with STO-609, but only at high concetration (50 μM). We subsequently treated LNCaP-mock and LNCaP-CaMKII-β transfectant cells 17 with DOX in the presence of si-AR and found that CaMKII-β overexpression protected p53-Ser15 expression (Fig. 3E).…”
Section: Resultsmentioning
confidence: 98%
“…We also showed that the expression of CaMKII genes is under the control of AR. 17 As a first approach to investigate the potential role of CaMKII in AR-mediated inhibition of p53, we used a specific CaMKII inhibitor, KN-93, and a non-specific analog, KN-92, as a control. In addition, we used STO-609, which is an inhibitor of CaMK-kinase and its two major downstream targets CaMKI and CaMKIV, 28 as well as an inhibitor of p38 kinase, SB202190.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations